2014
DOI: 10.1007/s10903-014-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Birth Weights and Related Factors of Native and Immigrant Residents of Spain

Abstract: Birth weight is a high impact factor in populations with high rates of immigration. This study establishes differences in birth weight (BW) and related factors among full-term newborn (NB) infants born to native and immigrant women living in Spain during 2007-2008. All NBs from Spanish mothers and mothers from the five nationalities with the highest birth rates in Spain (Morocco, Romania, Ecuador, Bolivia, and Colombia) according to the Statistical Bulletin of Births in Spain were included. BW was classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…En el país no se dispone de datos de macrosomía. En un estudio realizado en mujeres inmigrantes de diferentes países residentes en España se encontró que de un total de 8.544 mujeres colombianas, la macrosomía alcanzó 8,6% 8 .…”
unclassified
“…En el país no se dispone de datos de macrosomía. En un estudio realizado en mujeres inmigrantes de diferentes países residentes en España se encontró que de un total de 8.544 mujeres colombianas, la macrosomía alcanzó 8,6% 8 .…”
unclassified
“…The level of education of immigrants tended to be lower than that of native mothers ( Restrepo-Mesa et al., 2015 ; Racape et al., 2016 ). Bolivian and Paraguayan women had a similar profile, with the lowest educational level, dissimilar to Peruvians and Brazilians with a higher level.…”
Section: Discussionmentioning
confidence: 78%
“…Although the comparison of immigrant mothers in Brazil with those who live in other parts of the world should be made with reservations, owing to differences in immigration, social and environmental influences in the host country, a previous study observed a higher proportion of Bolivian mothers aged < 20 years (6.1%), compared to Spanish mothers (2.1%) ( Restrepo-Mesa et al., 2015 ). This lower frequency of Bolivian teen mothers living in Spain, compared with our results, suggested their adaptation to the Spanish social and reproductive standards.…”
Section: Discussionmentioning
confidence: 99%
“…One Canadian study found mixed results by geography, however: in one province, higher SES mothers had higher odds for macrosomia while lower SES mothers had higher odds in another province (Dubois et al, 2007). The few existing studies that have examined race, ethnicity, or nativity suggest that foreign-born mothers in the US and Europe tend to have higher birthweights and higher odds of macrosomia than their native-born counterparts, as well as an increased risk for gestational diabetes, which is predictive of higher birth weight (Forna et al, 2003; Juarez and Revuelta-Eugercios, 2014; Restrepo-Mesa et al, 2015). Yet a study in Michigan observed lower odds of giving birth to a macrosomic infant among immigrant mothers; this study did not, however, include important controls in the multivariate models, such as race (El-Sayed and Galea, 2011).…”
Section: Introductionmentioning
confidence: 99%